Local government’s revenue, audit opinion of BPK and financial performance of local government: Indonesia evidence - Aditya Indra Prayitno; Nova Novita (Proceedings of AICS - Social Sciences, 2013)
Decentralization or local autonomy is directed to stimulate the equalization distribution of development, improve the people’s welfare, encourage initiative and active participation of the society in a real. This study focuses on the impact of local goverment revenues (PAD) and audit opinion of BPK in financial performance. The Local government revenue’s (PAD) components consist of local taxes, local retribution, separated local asset and the others legal local revenue. While BPK’s audit opinión is dummy variable. The sample used in this study are 31 local government were categorized high level fiscal capacity during the period 2011-2012. Samples obtained from the local government financial statements (LKPD) BPK RI.Research result indicates that audit opinion of BPK is statistically significant to the financial performance of the local governments. While the local taxes show the negatives effect on financial performance, which is contrary to existing theories. This result shows that the management of local revenue in local government in Indonesia still not optimal yet.Keywords: Local Government revenues (PAD), audit opinion of BPK, financial performance, local governments